PENGARUH ETIKA AUDITOR DAN TEKANAN ANGGARAN WAKTU TERHADAP KUALITAS AUDIT APIP PADA INSPEKTORAT PROVINSI SUMATERA SELATAN - Pramatitoadi, Muhammad Robby; Dewata, Evada; Mubarok, M Husni (Jurnal Riset Terapan Akuntansi, 2024)
The purpose of this study is to determine the Auditor Ethics and Budget Time Pressure on the Quality of APIP Audits at the Inspectorate of South Sumatra Province. Probability sampling is used in the sample collection technique. The population is all employees of the Inspectorate of South Sumatra Province and the number of samples is 39 people. This type of quantitative research uses primary data. The analysis technique of this study uses multiple regression analysis. This study uses SPSS Version 25 software testing tools. The results of the study indicate that: Auditor Ethics have a positive and significant influence on audit quality with a threshold of 0.000 <0.05 and tcount> ttable (6.118> 2.030). Budget Time Pressure has a positive effect on audit quality with a threshold> ttable (2.553> 2.030) and a significance level of 0.015 <0.05. The contribution of this study is the variable Auditor Ethics and Budget Time Pressure at the Inspectorate of South Sumatra Province Keywords: Audit Quality, Auditor Ethics, Budget Time Pressure